EGS P22 Management of acute cholecystitis during the Covid-19 pandemic - A complete cycle. (7th December 2022) - Islam, Muhammad; Tan, Jay Roe; Oldfield, Frances; English, Louise; Al-Rashedy, Mohammed; Tandon, Ashutosh
Abstract: Background: Acute cholecystitis is a common surgical emergency. NICE guidelines recommend early laparoscopic cholecystectomy should be performed within 1 week of diagnosis. Emergency and elective surgical provision was affected during the first wave of the covid pandemic due to high postoperative mortality and pulmonary complications. The objectives of this audit were to assess and improve the local management of acute cholecystitis during the Covid-19 pandemic. Methods: A retrospective review of all patients who presented with acute cholecystitis over 2 months was performed in April 2020. Several interventions were introduced following the first cycle to improve our adherence with NICE guidelines, including 'green elective surgical pathway', clinical priority coding for elective surgeries, a hot gallbladder pathway, and a dedicated weekend and evening list. A re-audit was performed over 2 months in July 2020. These findings were presented at the departmental meeting. Results: 34 patients were reviewed in the first audit and 37 in the re-audit. A higher number of patients with acute cholecystitis in cycle 2 had admission covid swabs (97.3% vs 64.7%) and interval covid swabs (54.1% vs 0%) compared to cycle 1. One patient was tested positive for Covid-19 in cycle 2 and was listed for elective operation. Cycle 2 revealed a higher rate of hot gallbladder (from 8.8% to 10.8%) and a shorter median length from admission to operation (from 4 to 1.5 days). A higher rate of patients was readmitted due to complications of cholecystitis in cycle 2 (29.7% vs 20.6%) compared to cycle 1. Conclusions: The overall performance is still behind the NICE guideline recommendation. We have identified factors such as pressure on theatre facilities and resources and cancer fast-track priority surgeries during the Covid-19 pandemic. Ongoing audit and optimisation of the hot gallbladder pathway, elective surgical pathway, extra lists, and clinical priority of operations are important to improve the quality of care for patients with acute cholecystitis.